The web-based outpatient information system at community health center - Alvianita V.; Nguyen P.T.; Ilayaraja M.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Community Health Center is one of the agencies engaged in public health services. As technology advances in the health sector, an application is needed to accelerate and facilitate the Community Health Center in delivering information about Community Health Center and can be accessed by the public without limited space and time. Therefore this final project aims to provide information by improving the quality of Community Health Center by facilitating websites so that they can support the development of Community Health Center services. With the establishment of a Web-Based Outpatient Patient Information System at Talangpadang Community Health Center, it is hoped that it can facilitate the community to get the information needed, related to the Talangpadang Community Health Center. This application is Web-based, using the Web programming language, PHP, MySQL. BEIESP.